Traumatic Brain Injury Screening and the Unmet Health Needs of Shelter-Seeking Women with Head Injuries Related to Intimate Partner Violence - Linda Denise Oakley; Jeneile Luebke; Natalie C. Dosch; Traci R. Snedden; Hector Hernadez; Melissa Lemke; Rick P. Voland (Mary Ann Liebert, 2021)
Background: Unmet health needs of women with head injuries sustained by intimate partner violence (IPV) include risk of traumatic brain injury (TBI). The purpose of this evaluation was to explore the potential effectiveness of TBI screening as a health promotion strategy for shelter-seeking women with IPV head injuries. We wanted to learn if shelter-seeking women, willing to disclose IPV, would accept TBI screening if offered. Methods: An extended version of the HELPS TBI screening tool and survey of daily symptoms and health needs were used to screen new residents of an urban shelter for women. Results: The participants (N?=?18) primarily were educated black women with one or more self-reported IPV-related head injury. Most participants (77.8%) had positive TBI screens for probable brain injury. The majority (88.8%) lived with one or more daily symptoms they did not have before sustaining a IPV head injury. The symptoms reported most frequently were depression (88.9%), anxiety (77.8%), and headache (66.7%). All participants had one or more unmet health need. Although most (77.8%) needed to see a primary care provider, mental health care was the most important health need identified. Conclusions: TBI screening could be considered an effective health promotion strategy for IPV survivors if screening facilitates treatment for positive screens and other unmet health needs. Further research is needed to properly assess this.